ИННОВАЦИОННЫЕ ТЕХНОЛОГИИ НА УРОКАХ ФРАНЦУЗСКОГО ЯЗЫКА В НЕЯЗЫКОВЫХ ВУЗАХ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article highlights innovative technologies in teaching foreign languages in compliance with social evolution and 25 requirements of the curriculum of a non-linguistic institute. There is a scheme of the teaching French oral speech according some characteristics of a text and exercises necessary for mastering vocabulary. The article also covers the criteria for measuring knowledge at the end of the course.
Keywords: innovative technologies, teaching methods, internet resources, teaching foreign languages